Behavior of the Newborn during Skin-to-Skin. (August 2015) - Dani, Carlo; Cecchi, Alessandra; Commare, Arianna; Rapisardi, Gherardo; Breschi, Rita; Pratesi, Simone
Background: Early skin-to-skin contact (SSC) significantly increases the breastfeeding rate in healthy term infants. Objective: This study aimed to confirm previously described behavioral sequences during SSC. Methods: We recorded live and videotaped infant behavioral sequences during SSC in a cohort of healthy term infants, whose outcome was then evaluated. Results: We studied 17 mother-infants dyads. While the majority of infants (59%) had behavioral phases that have been previously reported, some of them had alternative sequences. We observed the infant's massage of the mother's breast with its hand during SSC, which had not been previously reported. We found no correlations between behavioral sequence during SSC, breastfeeding, and neonatal outcome. Moreover, maternal pain stimuli did not affect the neonatal SSC behavioral sequence. Conclusion: Our study confirms that immediate and undisturbed postpartum SSC is characterized by specific behavioral phases whose sequence may vary without affecting the suckling rate at the end of SSC, breastfeeding success, or the short-term neonatal outcome.